E-Learning Application Using the Jigsaw Method as A Mathematics Learning Media - Restu Ningsih, Sri; Darwas, Rahmadini; Rahimullaily; Irma Suryani, Ade (ENCRYPTION: Journal of Information And Technology, 2023)
This research aims to facilitate the process of learning mathematics online in high schools, to increase the efficiency of teachers and students in understanding and evaluating lessons and to make it easier for teachers and students to give and submit assignments. The method in this study is SDLC using the Waterfall method, using the PHP programming language and MySQL database. The problem that is being faced in schools is that the process of teaching and learning activities uses conventional methods, still using WhatsApp as an online learning medium, and teachers ask students to turn in assignments to be delivered to school. The results of this study are e-learning applications as a jigsaw-based Mathematics learning medium that is able to provide benefits for teachers and students in the process of learning mathematics and submitting assignments at the school.